Stabilisation measures on the de-occupied territories: conceptual interpretation, classification, and application features (Law and Safety, 2024)
The publication provides a scientific analysis of the “stabilisation measures” concept which has recently been used to determine the specifics of public authorities and law enforcement agencies' activities on the de-occupied territories of our country. It has been proved that the concept of “stabilisation measures” arose in the course of NATO peacekeeping operations in the Balkans and is primarily associated with law enforcement activities of specially authorised military units capable of performing police functions. According to NATO’s Joint Doctrine (AJP-3.22), stabilisation measures are defined as special activities aimed at strengthening or providing temporary replacement for local police forces to help restore and/or maintain public order and security, the rule of law and the protection of human rights.It is emphasised that the understanding of the content of stabilisation measures in national and foreign practice is different. Foreign researchers mainly associate stabilisation measures with law enforcement actions: ensuring public order and security, combating crime, protecting civilians, etc. In our country, a broader interpretation of the term has been formed, which, in addition to purely police measures, includes social, humanitarian, informational, and economic measures that cover the comprehensive restoration and development of the de-occupied territories.It is proposed to divide stabilisation measures into general and special ones. The first type is related to the restoration of state power on the de-occupied territory, as well as to ensuring the vital activity of its civilian population. Special stabilisation measures are carried out to prevent sabotage and reconnaissance groups and illegal armed groups from entering the de-occupied territory and committing terrorist acts on infrastructure and communications facilities, ensuring public safety and order, preventing and suppressing crimes and other offences, eliminating the consequences of emergencies, and searching for persons who have committed crimes against the foundations of national security, war crimes and other offences during the occupation of the territory.The number of conceptual provisions on the interpretation of the definition, purpose, principles, types and peculiarities of application of stabilisation measures in Ukraine have been formulated.
Keywords: martial law; stabilisation measures; public security; public order; civilian security; police; NATO; de-occupation.